KONSTRUKSI MAKNA MAROSOK DALAM TRANSAKSI JUAL BELI TERNAK DI DESA CUBADAK KABUPATEN TANAH DATAR - Putri, Jelly Dwi; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Marosok culture is a tradition/custom handed down captivate the generations that growing up until now in Cubadak area, Tanah Datar,West Sumatra Province. Marosok seen as full of philosophical traditions, values and philosophy of life of the Minangkabau. These values arise from the use of symbols modified legacy understood by the public as part of the social system of community life itself which is visible from the way of buying and selling cattle they do in the cattle market. This study focused on the knowledge of how the construction of meaning that arise in terms of both physical objects and social objects that exist in the community marosok.This research used qualitative approach to be supported by the theory of social construction of reality and Symbolic Interaction. The subjects were cattle sellers, buyers of livestock, and the society of the area. Informants selected by purposive sampling technique. The data obtained by interviews, observation, documentation, literature, and online data searches. The validity test of the data using the credibility test. The data analysis techniques were reducting the data, collect data, present data, make conclusions and evaluation.The results showed that marosok tradition not only regarded as the usual way of buying and selling,with use the tools to close the transaction to keep the secret of priceand also can be used as a polite way of trade, filled with mutual respect and manners. Because this kind of social interaction only done in Minangkabau and should be preserved as identity of Minangkabau society in particular.Keywords : construction of meaning, symbolic interaction, marosok.